Parathyridaria ephedrae sp. nov. (Thyridariacaeae, Pleosporales), endophytic to Ephedra gerardiana in India - Mattoo, Aroosa Jan; Nonzom, Skarma (Phytotaxa, 2022)
A novel endophyte, Parathyridaria ephedrae sp. nov. (Thyridariaceae) was isolated from the stem of Ephedra gerardiana growing in Kargil district of Union territory Ladakh, India. Detailed micromorphological investigations revealed that this isolate differs from previously described Parathyridaria species by having 1–3 wart-like prominent papillae, a larger ostiolar canal, thicker conidiomatal wall with more layers of textura angularis, and larger conidia. Phylogenetic analyses based on concatenated sequence datasets of internal transcribed spacer (ITS) regions and large subunit (LSU) of nuclear ribosomal DNA (nrDNA) strongly supported the morphological outcome and confirmed the novelty of the taxon. Detailed description, illustrations, and phylogenetic results of the novel species are presented and discussed.